Multisensory and closed kinetic chain exercises on the functional capacity and balance in elderly women: blinded randomized clinical trial - Luiz Gustavo Padovini Ferreira; Caio Vitor dos Santos Genebra; Nicoly Machado Maciel; Eduardo Aguilar Arca; Alexandre Fiorelli; Alberto De Vitta
Abstract Introduction: The aging process causes losses that lead to decreased balance, gait speed and functional capacity and, therefore, there is a need of specific protocols to work preventively these variables, which will contribute to the decrease in the frequency of falls in this population. Objective: Verify the effect of a program of multisensory and closed kinetic chain exercises on the functional capacity and balance in elderly women. Methods: Randomized clinical trial masked (blind). Subjects were 32 elderly women from the Centro de Convivência of the Bauru Department of Social Welfare (Secretaria de Bem-Estar Social de Bauru) distributed in two groups: control (CG = 15) and experimental (EG = 17). Interventions: The program of multisensory and closed kinetic chain exercises was applied during an hour, once a week, for 12 weeks. Main measures: Functional capacity was measured by Timed Up and Go (TUG) and the 10-meter walking test (TC10) and their balance by the Berg Balance Scale (BBS). Results: Regarding the comparison between the moments M1 and M2 of the EG after the intervention, there was a statistically significant increase in the functional capability (p = 0.00006), walking speed (p = 0.0008) and balance (p = 0.0006). Conclusion: The multisensory and closed kinetic chain-training program indicated a beneficial effect in the improvement of the elderly women balance and functional performance.